Management Measurement Scale As A Reference To Determine Interval In A Variable - Aini, Qurotul; Zuliana, Siti Ria; Santoso, Nuke Puji Lestari (Pandawan, 2018)
The scale is usually used to check and determine the value of a qualitative factor in quantitative measures. The measurement scale is a management in agreement that is used as a reference to determine the short length of the interval that is in the measuring instrument, so that the measuring instrument when used in measurements will produce quantitative data. The results of the scale management calculation must be interpreted carefully because in addition to producing a rough picture, the respondent's answers are not just straightforward to be trusted. Types of measurement scales: Likert scale, Guttman scale, semantic differential scale, rating scale, Thurstone scale, Borgadus scale, and various other measurement management scales. One of the most difficult jobs for information technology researchers faced with the necessity of measuring variables is: finding directions in the midst of many existing sizes. If there is a good size for a particular variable, it seems that there are not many reasons to compile a new size yourself. Keywords: Scale, Measurement, Variables.